Death Drive Through Gaia Paris - Noble, Charles (Open Spaces, 2007)
"Noble's work has always engaged, in its own way, with the Western Canadian tradition of poetry as intellectual experiment grounded on local experience.... Death Drive marks a counter-turn in the work of one of Southern Alberta's most distinctive writers." - Chris Jennings, Department of English, University of Ottawa In this collection of poetry, Charles Noble further reins in an already tight form - haiku - only to let loose a "logopoeic" poetry. He presents poems of extraordinary rigour and riddles of wit that are solved by "lifetime" insights - a dialectical poetry that still observes a phenomenological toehold but transcends the limits of locality in recognizing the curled-up-but-everywhere world of media and markets - à la Fredric Jameson. And yet, these "haikus" go straight - to "the shock of the naïve." They turn to a middle ground, in Aristotle's sense of difficult target. They point to human acts, human reactions, and enact, themselves, a meta-linguistic wrestling, at one with the quarreling couple in the bar hanging on each other's words and insistent with "what do you mean by [a simple word]?" But they are also implicated in what he calls the death drive (not death wish), which arcs freely over a human life span - think architecture - and which, more radically, in the "pleated/ crossword," "make[s]/ good// a/ bit/ of/ bad/ infinity," no expenses, save for that toehold, earth, as he would have it.